2016
DOI: 10.1186/s13073-016-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

Sub-clinical detection of gut microbial biomarkers of obesity and type 2 diabetes

Abstract: BackgroundObesity and type 2 diabetes (T2D) are linked both with host genetics and with environmental factors, including dysbioses of the gut microbiota. However, it is unclear whether these microbial changes precede disease onset. Twin cohorts present a unique genetically-controlled opportunity to study the relationships between lifestyle factors and the microbiome. In particular, we hypothesized that family-independent changes in microbial composition and metabolic function during the sub-clinical state of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(147 citation statements)
references
References 60 publications
7
137
1
2
Order By: Relevance
“…We observed that Ruminococcus torques , involved in mucus degradation and gut barrier dysfunction [58], positively correlated with the increase in SBP. Furthermore, both Eubacterium siraeum and A. finegoldii , known to trigger intestinal inflammation [59,60], positively correlated with SBP. Although further validation is needed, this suggests that certain gut bacteria may drive intestinal gut barrier dysfunction and inflammation, which was confirmed by measurement of plasma markers and gut-targetted proinflammatory cells (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that Ruminococcus torques , involved in mucus degradation and gut barrier dysfunction [58], positively correlated with the increase in SBP. Furthermore, both Eubacterium siraeum and A. finegoldii , known to trigger intestinal inflammation [59,60], positively correlated with SBP. Although further validation is needed, this suggests that certain gut bacteria may drive intestinal gut barrier dysfunction and inflammation, which was confirmed by measurement of plasma markers and gut-targetted proinflammatory cells (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…43 Furthermore, in a study of the microbiome in new-onset CD, an exploratory analysis of genomes of organisms associated with CD identified a contribution to pathway components that included a zinc-dependent enzyme. 6 We therefore hypothesized that the SLC39A8 genetic variant identified in this study may affect CD susceptibility by altering the microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…88 Previous profiles of the gut microbiome in T2D have found compositional changes between patients and healthy controls, showing increased capacity for oxidative stress resistance and a decreased capacity for flagellar assembly and riboflavin metabolism. 89,90 However, the human microbiome contains vast numbers of uncharacterized enzymes, limiting our functional understanding of this community and its effects on host health and disease.…”
Section: Subclassification Of Type 2 Diabetesmentioning
confidence: 93%